Application of methods of mathematical statistics to optimize the composition of protective coatings - Buketov, A.V.; Akimov, A.V.; Nigalati, V.D.; Brailo, N.V.; Al-Dzhavakheri, Ali Andan Mansur (Bulletin of the Karaganda University. Mathematics Series, 2017)
In the method of mathematical statistics determined the optimal content of the polymer composite material modifier, ultrafine diamond and fine lithium carbonate filler to form an adhesive and the functional layers of the protective coating. During the experiment, we studied the effect of three factors (additive contents) on the physical and mechanical (flexural modulus, impact strength) and thermal (heat resistance according to Martens, the thermal coefficient of linear expansion) properties of the composites. We prove the adequacy of the obtained models and their consistency with the results of the optimization by the criterion of desirability.